In-situ vaccination using focused ultrasound heating and anti-CD-40 agonistic antibody enhances T-cell mediated local and abscopal effects in murine melanoma - Singh, Mohit Pratap (Int J Hyperthermia, 2019)
The success of melanoma immunotherapy is dependent on the presence of activated and functional T-cells in tumors. The objective of this study was to investigate the impact of local-focused ultrasound (FUS) heating (~42–45°C) and in-situ anti-CD-40 agonistic antibody in enhancing T-cell function for melanoma immunotherapy. We compared the following groups of mice with bilateral flank B16 F10 melanoma: 1) Control, 2) FUS, 3) CD-40, and 4) CD-40+FUS (FUS40). FUS heating was applied for ~15min in right flank tumor, and intratumoral injections of CD-40 were performed sequentially within 4h. A total of 3 FUS and 4 anti-CD-40 treatments were administered unilaterally 3 days apart. Mice were sacrificed 30 days post-inoculation, and the treated tumor and spleen tissues were profiled for T-cell function and macrophage polarization. Compared to all other groups, histology and flow cytometry showed that FUS40 increased the population of tumor-specific CD-4+ and CD-8+ T cells rich in Granzyme B+, interleukin-2 (IL-2) and IFN-γ production and poor in PD-1 expression. In addition, FUS40 promoted the infiltration of tumor-suppressing M1 phenotype macrophages in the treated mice. The resultant immune-enhancing effects of FUS40 suppressed B16 melanoma growth at the treated site by 2-3-folds compared to control, FUS, and CD-40, and also achieved significant abscopal effects in untreated tumors relative to CD40 alone. Additionally, the local FUS40 prevented adverse liver toxicities in the treated mice. Our study suggests that combined FUS and CD-40 can enhance T-cell and macrophage functions to aid effective melanoma immunotherapy.